Self-Care Management of Diabetes Patients in the Community Health Center Area - Diani, Noor; Nurachmah, Elly; Dahlia, Debie; Martha, Evi; Noor, M. Fakhruddin; Nafi'ah, Rizka Hayyu (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
The success of diabetes prevention is influenced by several factors, including access to information, family support, diet, activity patterns, nutritional status, and self-efficacy. These factors play a significant role in the self-care practices of individuals with diabetes. Self-care refers to actions taken by patients to improve their ability to meet their daily needs independently, enabling them to prevent and manage their illness and adhere to treatment and recommendations provided by healthcare services. This study aims to identify the self-care practices of individuals with diabetes. The research involved 40 respondents diagnosed with diabetes. The average self-care score among diabetic patients in the working area of Banjar Baru Selatan Community Health Center was 68.53, with the lowest score being 39 and the highest score 92. Establishing self-care behaviors as part of a cultural norm requires consistent repetition and routine, to the extent that these behaviors may eventually become secondary needs. One approach to cultivating such habits in individuals with diabetes is to focus on addressing their weaknesses through methods that align with their routines and learning patterns. This strategy can help foster motivation and enthusiasm in managing their condition.